DNA adducts and chronic degenerative diseases: pathogenetic relevance and implications in preventive medicine - DeFlora, Silvio; Izzotti, Alberto; Randerath, Kurt; Randerath, Erika; Bartsch, Helmut; Nair, Jagadeesan; Balansky, Roumen; van Schooten, Frederikjan; Degan, Paolo; Fronza, Gilberto; Walsh, Debra; Lewtas, Joellen (Mutation research. Reviews in mutation research, 1996)
Chronic degenerative diseases are the leading causes of death in developed countries. Their control is exceedingly difficult due to their multiplicity and diversity, the interconnection with a network of multiple risk factors and protective factors, the long latency and multistep pathogenesis, and the multifocal localization. Adducts to nuclear DNA are biomarkers evaluating the biologically effective dose, reflecting an enhanced risk of developing a mutation-related disease more realistically than the external exposure dose. The localization and accumulation of these promutagenic lesions in different organs are the composite result of several factors, including (a) toxicokinetics (first-pass effect); (b) local and distant metabolism; (c) efficiency and fidelity of DNA repair; and (d) cell proliferation rate. The last factor will affect not only the dilution of DNA adducts but also the possible evolution towards either destructive processes, such as emphysema or cardiomyopathies, or proliferative processes, such as benign or malignant tumors at various sites. They also include heart tumors affecting fetal myocytes after transplacental exposure to DNA-binding agents, blood vessel tumors, and atherosclerotic plaques. In this article, particular emphasis is given to molecular alterations in the heart, which is the preferential target for the formation of DNA adducts in smokers, and in human aorta, where an extensive molecular epidemiology project is documenting the systematic presence of adducts to the nuclear DNA of smooth muscle cells from atherosclerotic lesions, and their significant correlation with known atherogenic risk factors. Exocyclic DNA adducts resulting from lipid peroxidation, and age-related indigenous adducts (I-compounds) may also originate from endogenous sources, chronic infections and infestations, and inflammatory processes. Type II I-compounds are bulky DNA lesions resulting from oxidative stress, whereas type I I-compounds are presumably normal DNA modifications, which display positive correlations with median life span and are decreased in cancer and other pathological conditions. Profiles of type I I-compounds strongly depend on diet and are related to the antidegenerative effects of caloric/dietary restriction. Even broader is the possible meaning of adducts to mitochondrial DNA, which have been detected in rodents exposed to genotoxic agents and complex mixtures, as well as in untreated rodents, in larger amounts when compared to the nuclear DNA of the same cells. Mutations in mitochondrial DNA increase the number of oxidative phosphorylation-defective cells, especially in energy-requiring postmitotic tissues such as brain, heart and skeletal muscle, thereby playing an important role in aging and a variety of chronic degenerative diseases. A decreased formation of DNA adducts is an indicator of reduced risk of developing the associated disease. Therefore, these molecular dosimeters can be used as biomarkers in the prevention of chronic degenerative diseases, pursued either by avoiding exposure to adduct-forming agents or by using chemopreventive agents. Interventions addressed to the human organism by means of dietary measures or pharmacological agents have encountered a broad consensus in the area of cardiovascular diseases, and are deserving a growing interest also in cancer prevention. The efficacy of chemopreventive agents can be assessed by evaluating inhibition of nuclear DNA or mitochondrial DNA adduct formation in vitro, in animal models, and in phase II clinical trials in high-risk individuals.
Elektronische Reproduktion der Druck-Ausgabe 3. November 2002
Gesehen am 10.01.2024